Novel poly(l‐lactide)/poly(d‐lactide)/poly(tetrahydrofuran) multiblock copolymers with a controlled architecture: Synthesis and characterization. Issue 22 (19th September 2014) - Gardella, Lorenza; Cavallo, Dario; Colonna, Samuele; Fina, Alberto; Monticelli, Orietta
ABSTRACT Novel poly(l‐lactide) (PLLA)/poly(d‐lactide) (PDLA)/poly(tetrahydrofuran) (PTHF) multiblock copolymers with designed molecular structure were synthesized by a two‐stage procedure. Well‐defined PDLA‐PLLA‐PTHF‐PLLA‐PDLA pentablock copolymers were prepared by sequential ring opening polymerization of l‐ and d‐lactides starting from PTHF glycol, with the length of the (equimolar) PLLA and PDLA blocks being varied. Then, these dihydroxyl‐terminated pentamers were transformed into multiblock copolymers by melt chain‐extension with hexamethylene diisocyanate–being the first time that the coupling of pentablock units is reported. The successful formation of macromolecular chains with a multiblock and well‐defined architecture was demonstrated by 1H NMR spectroscopy. The thermal properties and structuring of the resulting materials were investigated by means of DSC and WAXD measurements and DMA analysis. Stereocomplexation was found to be promoted during solution and melt crystallization. This approach affords materials combining the high rigidity and strength (other than improved thermal resistance) of the hard stereocomplex crystallites with the flexibility imparted by the soft block, whereby their properties can be finely tailored through the composition of the basic pentablock units without limitations on the final molecular weight. The adopted reaction conditions make this process highly appealing in view of the possibility to perform it in extruder. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 3269–3282